Phenotypic and functional differentiation of porcine αβ T cells: Current knowledge and available tools. Issue 1 (July 2015) - Gerner, Wilhelm; Talker, Stephanie C.; Koinig, Hanna C.; Sedlak, Corinna; Mair, Kerstin H.; Saalmüller, Armin
Highlights Porcine CD4+ memory T cells have a peculiar CD4+CD8α+ phenotype. Lung-derived porcine CD4+ T cells are potent IFN-γ and IL-17A producers. IL-2 producing CD4+ and CD8β+ T cells are enriched in lymph nodes.